Great writers on organizations - Pugh, Derek Salman; Hickson, David John. (Aldershot ; Brookfield, USA : Ashgate, 2000)
A collection of the thoughts of many great writers on organizations. These writers are from a variety of different backgrounds. All have attempted to draw together information and distil theories about how organizations function and how they should be managed.
Includes bibliographical references and indexes.
oif 11/08/15
Loan
Keywords: Organizational sociology; Industrial management